CSC792: Web Intelligence / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2017)
Ever increasing influx of information on the web has provided immense source of information. It is thus important to construct intelligent and innovative web technology to satisfy the need of future generations. This course covers all aspects of designing intelligent web technology.